2009
DOI: 10.5897/ajpp10.390
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alpha-lipoic acid and time-of-day on interleukin-6 response to exhaustive exercise in humans

Abstract: Circadian rhythms have an influence on human performance. Interleukin-6 is a cytokine which plays a role in muscle energy homeostasis during physical exercise. This study tested the effect of diurnal variation and alpha-lipoic acid, a natural thiol antioxidant, on skeletal muscle contractile properties, interleukin-6 response and oxidative damage. Male subjects (n=26) performed isokinetic exercise in different time-of-day. Next, the subjects were supplemented with alpha-lipoic acid for two weeks and the exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…However its effects on isokinetic exercise performance are unknown. A recent study suggests that vitamin E and α-lipoic acid supplementation may in fact suppress skeletal muscle mitochondrial biogenesis, regardless of training status ( 70 ). Some studies have shown the benefits of lipoic acid or vitamin E supplementations in endurance trained horses ( 71 ).…”
Section: Resultsmentioning
confidence: 99%
“…However its effects on isokinetic exercise performance are unknown. A recent study suggests that vitamin E and α-lipoic acid supplementation may in fact suppress skeletal muscle mitochondrial biogenesis, regardless of training status ( 70 ). Some studies have shown the benefits of lipoic acid or vitamin E supplementations in endurance trained horses ( 71 ).…”
Section: Resultsmentioning
confidence: 99%
“…IL-6 is a cytokine which plays a role in muscle energy homeostasis during physical exercise. Lappalainen [88] investigated the effect of LA administration on IL-6. IL-6 is an immunomodulatory cytokine produced mainly by the cells of the immune system and is considered as a marker of inflammation.…”
Section: Alpha-lipoic Acidmentioning
confidence: 99%
“…IL-6 can improve skeletal muscle energy supply and assist in the maintenance of stable blood glucose levels by stimulating lipolysis in the adipose tissue and augmenting hepatic glycogenolysis [90,91]. Lappalainen [88] has indicated that exercise increases serum IL-6 levels irrespective of diurnal variation and showed that supplementation with LA had no beneficial effect on exercise performance and exercise-induced IL-6 response. Some publications also presents a beneficial effect of supply LA in the haematological context.…”
Section: Alpha-lipoic Acidmentioning
confidence: 99%